2020
DOI: 10.2169/internalmedicine.4113-19
|View full text |Cite
|
Sign up to set email alerts
|

Refractory Right Ventricular Failure in a Patient with Emery-Dreifuss Muscular Dystrophy

Abstract: A 23-year-old man had progressive muscle weakness and Emery-Dreifuss muscular dystrophy (EDMD) due to a LMNA (lamin A/C) mutation. Congestive heart failure diagnosed at 19 years of age. Maximal drug treatment/cardiac resynchronization failed to improve the cardiac function. He was therefore hospitalized due to heart failure. Despite extracorporeal membrane oxygenation, he developed severe right heart dysfunction and died (multiple organ failure). A cardiac lesion's presence determines the prognosis of EDMD. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
(9 reference statements)
0
2
0
1
Order By: Relevance
“…However, it should be noted that patients with EDMD1 may also develop dilated cardiomyopathy in the course of the disease. [6][7][8][9][10] Boriani G et al reported that left ventricular dilation/ hypokinesia was observed in two of the five patients with EDMD1 at the age of 50 years or older. 6 In a study by Bialer et al, 7 all seven affected male patients with EDMD1 at the age of 35 years or older had cardiac conduction abnormalities requiring pacemakers, and two of them developed cardiomyopathy thereafter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be noted that patients with EDMD1 may also develop dilated cardiomyopathy in the course of the disease. [6][7][8][9][10] Boriani G et al reported that left ventricular dilation/ hypokinesia was observed in two of the five patients with EDMD1 at the age of 50 years or older. 6 In a study by Bialer et al, 7 all seven affected male patients with EDMD1 at the age of 35 years or older had cardiac conduction abnormalities requiring pacemakers, and two of them developed cardiomyopathy thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of refractory VT/VF, only a LVAD and heart transplantation can prevent sudden cardiac death. [8][9][10] In Japan, waiting period for heart transplantation is usually long because of the shortage of donors, but LVAD can be implanted as bridge to heart transplantation. Thus, considering heart transplantation is necessary when heart failure is progressive and/or refractory VT/VF appears.…”
Section: Discussionmentioning
confidence: 99%
“…Fonte: Autores.4. Discussão(Achmad et al, 2017;Binder et al, 2020;Blagova et al, 2016;Borch et al, 2022;Brisset et al, 2019;Calame et al, 2021;Carboni et al, 2008;Carboni et al, 2012;Chen et al, 2017;Chiba et al, 2020;Cotta et al, 2019;Coutance et al, 2012;Dai et al, 2020;Dell'Amore et al, 2007;Deymeer et al, 1993;Di Blasi et al, 2000; Douglas et al, 2022; Dumitru et al, 2021;Duras et al, 2022;Ellis et al, 1999;Ellis et al, 2000;Felice et al, 2000;Fidzianska et al, 2010;Finsterer et al, 2015;Fujimoto et al, 1999;Fujita et al, 2005;Ghosh & Milone, 2014; Giuca et al, 2020;Golzio & Chiribiri, 2007;Gossios et al, 2013; Hausmanowa-Petrusewic et al, 2015;Higuchi et al, 2005;Hoeltzenbein et al, 1999;Homma et al, 2018;Hong et al, 2005;Huang et al, 2020; Ichkawa et al, 1997;Ishikawa et al, 2011;Iskandar et al, 2022;Jimenez-Escrig et al, 2012;Kalin et al, 2019; Karst et al, 2009; Kichuk et al, 2002; Köbel et al, 2018; Ki et al, 2022;Kim et al, 2008;Kovalchuk et al, 2021; Lassuthová et al, 2009;Lee et al, 2020;…”
unclassified